Memory-enhancing, Antioxidant, and Anticholinesterase Effects of Inhaled Achillea pseudoaleppica Essential Oil on Scopolamine-induced Amnesic Rats - Akbaba, Emel; Bagci, Eyup (Taylor & Francis Ltd, 2022)
Achillea species are used for therapeutic purposes in many countries. This study demonstrated the memory-enhancing, antioxidant, and anticholinesterase effects of Achillea pseudoaleppica essential oil in scopolamine-induced amnesia. The GC/FID-GC/MS system revealed camphor as the major compound in the oil. The application of the essential oil (1% and 3%) was performed on the rats by inhalation for 21 consecutive days before the performance of the behavioral tests (Y-maze and radial-arm maze tests). The essential oil application increased the spontaneous alternation behavior in scopolamine-induced rats in the Y-maze task. Furthermore, essential oil administration decreased working memory errors and reference memory errors in scopolamine-treated rats in the radial-arm maze test. Therefore, Achillea pseudoaleppica essential oil inhalation improved memory in scopolamine-treated rats. In addition, acetylcholinesterase and antioxidant profiles of the hippocampal tissues of the rats were examined. Essential oil administration decreased acetylcholinesterase and superoxide dismutase specific activities and malondialdehyde levels while increasing the total content of reduced glutathione in the rat hippocampus in scopolamine-treated rats. Therefore, in this study, the combination of scopolamine and Achillea pseudoaleppica essential oil improved memory formation and increased the activities of antioxidants and anticholinesterase.
Keywords: Achillea pseudoaleppica essential oil; Scopolamine; Memory; Y-maze; Radial-arm maze